Copy number variation in neuropsychiatric disorders - Marshall, Christian (Henry Stewart Talks, 2009)
Copy Number Variation (CNV) in the human genome, General characteristics, Detection methodologies, Copy number variation and human disease, Cataloguing and assessing the biological impact of a copy number variant, The genetic basis of Autism spectrum disorder (ASD) and the role of CNVs in ASD etiology, Variable neuropsychiatric phenotypes associated with copy number variation, Diagnostic and interpretation challenges